Fighting HIV/AIDS in the Caribbean - Marquez, Patricio (World Bank, Washington, DC, 2012)
In the Caribbean, HIV/AIDS has become the major cause of death among men under the age of 45. Official figures show more than 360,000 people living with AIDS, but estimates place the number at over 500,000 due to underreporting. More than 80,000 children have been orphaned by the epidemic, and the infection rate is estimated to have reached 12 percent in some urban areas, spreading in many countries from high-risk groups to the general population. The Caribbean Regional Strategic Plan of Action for HIV/AIDS will support national programs based on the countries' own needs. While the general population will benefit from a reduction in the rate of new infections, the program will particularly benefit high-risk groups and the 300,000-500,000 people living with HIV/AIDS, by increasing their care quality and coverage. The program (see Table 1, on back page) will focus its support on a participatory approach to facilitate government work in partnership with patients, community groups, religious organizations, NGOs, health professionals and the private sector. The five-year program includes: Communications campaigns to raise awareness; scaling up prevention activities, at the national and community levels; strengthening care of people living with HIV/AIDS by improving treatment, including sexually transmitted infections and opportunistic infections like tuberculosis; supporting research and surveillance; and capacity building to improve program coordination and resource management.